2020
DOI: 10.1126/science.abc4776
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection protects against rechallenge in rhesus macaques

Abstract: An understanding of protective immunity to SARS-CoV-2 is critical for vaccine and public health strategies aimed at ending the global COVID-19 pandemic. A key unanswered question is whether infection with SARS-CoV-2 results in protective immunity against re-exposure. We developed a rhesus macaque model of SARS-CoV-2 infection and observed that macaques had high viral loads in the upper and lower respiratory tract, humoral and cellular immune responses, and pathologic evidence of viral pneumonia. Following init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

70
1,016
8
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 861 publications
(1,109 citation statements)
references
References 20 publications
70
1,016
8
9
Order By: Relevance
“…There have been anecdotal accounts suggesting that immunity generated from an initial SARS-CoV-2 infection in humans may not be protective against a subsequent infection. Recent studies using nonhuman primates indicated prior infection results in protective immunity (19). Here, we…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…There have been anecdotal accounts suggesting that immunity generated from an initial SARS-CoV-2 infection in humans may not be protective against a subsequent infection. Recent studies using nonhuman primates indicated prior infection results in protective immunity (19). Here, we…”
Section: Discussionmentioning
confidence: 73%
“…The ongoing pandemic has led to the search for animal models faithfully recapitulating salient features of human coronavirus disease (COVID- 19) for pathogenesis studies and evaluation of vaccines and therapeutics (1). Early reports indicated that Syrian hamsters, whose ACE2 is highly homologous to its human ortholog, were highly susceptible to SARS-CoV-2 infection but did not develop severe disease (2,3).…”
Section: Main Textmentioning
confidence: 99%
“…During the SARS and MERS outbreaks, NHP models were developed with a moderate degree of success 3 . Early reports also indicate the utility of NHPs for SARS-CoV-2 infection, and for evaluating vaccine candidates 4, 5, 6, 7 . We hypothesized that the heterogeneity of human responses to SARS-CoV-2 infection can be recapitulated using multiple NHP species.…”
Section: Mainmentioning
confidence: 99%
“…This has important implications for COVID-19 vaccine development as virus-specific T cells are thought to play an important role in SARS-CoV-2 infection [18][19][20][21][22] . While no correlate of protection has been defined for COVID-19, recent publications suggest that neutralising antibody titres may be correlated with protection in animal challenge models 23,24 . A single dose of ChAdOx1 nCoV-19 induces antibody responses, but we demonstrate here that antibody responses are significantly enhanced after homologous boost in one mouse strain and to a greater extent in pigs.…”
Section: Discussionmentioning
confidence: 99%